The complete mitochondrial genome of Limassolla lingchuanensis (Hemiptera: Cicadellidae: Typhlocybinae) - Yuan, Xiaowei (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome of the leafhopper Limassolla lingchuanensis was determined. It is 15,716 bp in length and consists of 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, 2 rRNA genes, and a putative control region. ATN and TTG were initiation codons, and TAA, TAG, and T were termination codons. The phylogenetic relationships based on the neighbor-joining method were revealed using 13 PCGs with 10 leafhopper species of family Cicadellidae, which agree with the conventional taxonomy.